Determinants of Asset Misappropriation: An Empirical Testing of the Fraud Diamond Theory Model - Hartono, Rudi (Hikamatzu | Journal of Multidisciplinary, 2025)
This study discusses the critical issue of asset misappropriation in the public sector, a phenomenon that significantly undermines institutional integrity and the country's financial stability. The purpose of this study is to empirically analyze the influence of pressure, opportunity, rationalization, and capability on asset misappropriation in government organizations. This study uses quantitative methodology; data collected from 137 public sector employees in Semarang City and analyzed through Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) using SmartPLS 4.0. The results show that the four variables, namely pressure, opportunity, rationalization, and capability, have a positive and significant effect on asset misappropriation